National Health Insurance: Some Costs and Effects of Mandated Employee Coverage - Mitchell, Bridger M.; Phelps, Charles E. (Journal of Political Economy, 1976)
This paper assesses some economic consequences of financing national health insurance by mandating that employers provide insurance for their employees and dependents. Effects in 1975 are simulated using data from a 1970 health care survey. The findings are as follows: (1) Employer premiums would rise between 5 and 21 billion for plans under congressional consideration. (2) Without offsetting subsidies, these premium increases will cause a transitory increase in unemployment of 0.4-1.4 percentage points. (3) As employer premium payments are shifted to employees, taxable income will fall, leading to additional tax expenditures of 1.3-5.9 billion. (4) Tax expenditure on existing subsidies to health insurance is $6.4 billion.